Different variations of the karate technique Mawashi-Geri - Emmermacher, P.; Witte, K.; Bystryzycki, S.; Potenberg, J. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The aim of this pilot study is the characterisation of the foot moving trajectories of different variations of the Mawashi-Geri. By means of the VICON system with a sample rate of 250 fps a kinematical analysis was carried out. An essential finding was that only in the final phase of the movement the shape of the trajectory is a semicircle. From the statistical results it is concluded, that the amount of the foot trajectory is shorter when the technique is executed by the front leg than by the back leg. Even though no differences of the moving time were found. For all subjects higher maximal values of the foot velocity were determined in the case of using the back leg.